A4 Developing a prioritised vehicle equipment check-sheet (VECS): a modified Delphi Study. Issue 11 (14th October 2011) - Duncan, E; Fitzpatrick, D
Abstract : Background: The number, type; and complexity of equipment carried on frontline ambulances is increasing each year. While this enhances the range of prehospital interventions available, it also results in lengthy equipment checks which, on occasion, are interrupted by emergency calls. This can lead to ambulances arriving at an incident without vital equipment, or with equipment that malfunctions. Although equipment check-sheets have previously been developed to support ambulance clinicians, an informal audit of Scottish Ambulance Service practice indicated that these were outdated, un-prioritised and not in routine use. Methods: Aim: To develop a prioritised vehicle equipment check-sheet for routine use. Participants: 99 ambulance clinicians were purposively selected and invited to participate. Design: A modified Delphi study was undertaken. A list of all routine ambulance equipment was collated and developed into the initial Delphi study questionnaire. Participants were then asked to prioritise each item (on a scale from 1 [low priority] to 7 [high priority]) in two rounds. The questionnaire was distributed and returned by email. Analysis: Means and SDs were calculated for each item from round two. Results: 27 participants completed both rounds of data collection. Items which were required for life saving intervention rated the highest. These were followed by items relating to personal protection and infection control. Conclusions and Recommendations: This study has enabled the development of a prioritised vehicle equipment check-sheet with high face validity. Its prioritised nature means that vital equipment is accounted for first, ensuring their presence and functionality even if the vehicle is dispatched before a full check can be completed. The check-sheet is now being introduced throughout the Scottish Ambulance Service and would have applicability to other emergency medical services.